LITERASI PEMAHAMAN SEKURITAS PASAR MODAL UNTUK PEMULA PADA TINGKAT SMA - Hastuti, Rini Tri; Natasya Jusuf; Billy Christian (Jurnal Serina Abdimas, 2025)
For students in school, the term bonds is more foreign to them than the term stocks, because stocks are mentioned more often. However, in reality, stocks and bonds are important instruments for companies and investors. The PKM topic that we will implement is training on the importance of knowledge and understanding of Bond Securities Investment for Beginners. The topic given in this PKM activity is very important for two reasons: First, the material on investment in the form of bonds is not included in the basic accounting lesson material provided. Second, for students who have graduated and immediately entered the world of work, this investment material provision can be useful and support student literacy if they work in financial institutions. For that, we, the lecturers from the Faculty of Economics, will provide training which is planned to be divided into three stages, namely: the planning stage, the implementation stage, and the review stage. In the planning stage, we came to the partner to conduct a preliminary survey by interviewing teachers and principals. From this survey, we found a training topic that matched the partner's needs and we also prepared a proposal to LPPM. Furthermore, in the implementation stage, we conducted training by preparing training materials in the form of Modules that would be distributed during face-to-face training. The training lasted for one day. Finally, in the review stage, we will give quizzes and distribute questionnaires to students to determine their level of understanding of this topic. The output targets to be achieved from this training activity are: Outputs in the form of publications in Serina journals, HKI and Modules ABSTRAK Bagi murid-murid di bangku sekolah, istilah sekuritas obligasi lebih asing bagi mereka daripada istilah saham, dikarenakan saham lebih banyak disebut-sebut. Namun kenyataannya saham dan sekuritas obligasi merupakan instrumen penting bagi perusahaan dan juga investor. Topik PKM yang akan kami laksanakan adalah pelatihan mengenai pentingnya pengetahuan dan pemahaman investasi surat berharga sekuritas obligasi bagi pemula. Topik yang diberikan dalam kegiatan PKM ini sangat penting karena dua alasan: Pertama, materi mengenai investasi dalam bentuk sekuritas obligasi belum termasuk ke dalam materi pelajaran akuntansi dasar yang diberikan. Kedua, siswa yang telah lulus dan langsung terjun ke dunia kerja, pembekalan materi investasi ini dapat bermanfaat dan mendukung literasi siswa apabila bekerja di lembaga keuangan. Untuk itu kami, para dosen dari Fakultas Ekonomi dan Bisnis, akan memberikan pelatihan yang rencananya akan dibagi dalam tiga tahap, yaitu: tahap perencanaan, tahap pelaksanaan, dan tahap review. Pada tahap perencanaan, kami datang ke pihak mitra untuk melakukan survei pendahuluan dengan cara wawancara dengan guru-guru dan kepala sekolah. Dari survei ini, kami menemukan topik pelatihan yang cocok dengan kebutuhan mitra dan kami pun menyusun proposal ke LPPM. Selanjutnya, pada tahap pelaksanaan, kami melakukan pelatihan dengan menyiapkan materi pelatihan dalam bentuk modul yang akan dibagi pada saat tatap muka pelatihan. Pelaksanaan pelatihan berlangsung selama satu hari. Terakhir pada tahap review, kami akan memberikan kuis dan membagikan kuesioner kepada siswa-siswi untuk mengetahui tingkat pemahaman mereka atas topik ini. Luaran kegitan PKM ini berupa publikasi artikel pada jurnal Serina Abdimas, HKI dan modul.